2022
DOI: 10.1001/jamanetworkopen.2021.43597
|View full text |Cite
|
Sign up to set email alerts
|

Association of Area-Level Socioeconomic Deprivation With Hypoglycemic and Hyperglycemic Crises in US Adults With Diabetes

Abstract: IMPORTANCESocial determinants of health play a role in diabetes management and outcomes, including potentially life-threatening complications of severe hypoglycemia and diabetic ketoacidosis (DKA) or hyperglycemic hyperosmolar state (HHS). Although several person-level socioeconomic factors have been associated with these complications, the implications of area-level socioeconomic deprivation are unknown. OBJECTIVE To examine the association between area-level deprivation and the risks of experiencing emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…The present study demonstrated that higher neighborhood disadvantage, measured with a composite of diverse neighborhood-level socioeconomic indicators, is strongly predictive of more severe mTBI-related symptom burden from the acute (<24 hours) to the chronic (6 months) postinjury period. This mirrors findings supporting neighborhood disadvantage as uniquely related to diverse health outcomes outside the field of TBI39–41 and advances previous mTBI work on preinjury factors by establishing neighborhood disadvantage as a distinct contextual factor influencing injury presentation and outcome. In particular, individuals in the highest quartile of the ADI (per the national normative percentile score) reported more severe mTBI-related symptoms than individuals in the lower 3 quartiles.…”
Section: Discussionsupporting
confidence: 77%
“…The present study demonstrated that higher neighborhood disadvantage, measured with a composite of diverse neighborhood-level socioeconomic indicators, is strongly predictive of more severe mTBI-related symptom burden from the acute (<24 hours) to the chronic (6 months) postinjury period. This mirrors findings supporting neighborhood disadvantage as uniquely related to diverse health outcomes outside the field of TBI39–41 and advances previous mTBI work on preinjury factors by establishing neighborhood disadvantage as a distinct contextual factor influencing injury presentation and outcome. In particular, individuals in the highest quartile of the ADI (per the national normative percentile score) reported more severe mTBI-related symptoms than individuals in the lower 3 quartiles.…”
Section: Discussionsupporting
confidence: 77%
“…The outcomes of patients with hyperglycaemic crisis can be attributed to various complex factors, including pathological, psychological and socioeconomical factors. Insurance status is a key indicator of socioeconomical factors and has become an important determinant of the use of medical services 6 . In the US population, uninsured adults have two times the possibility of having DM than insured ones 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Insurance status is a key indicator of socioeconomical factors and has become an important determinant of the use of medical services. 6 In the US population, uninsured adults have two times the possibility of having DM than insured ones. 7 Having health insurance is the strongest predictor of whether adults with DM have access to diabetes screenings and care.…”
mentioning
confidence: 99%
“…Higher ADIs have been associated with lower-quality postoperative care, with subsequent additional barriers that hinder the ability of patients to receive future orthopedic-related care 16,17 . Furthermore, ADI and SES are correlated to increased comorbidity indices in populations disparaged by socioeconomic inequities 18–20 . Finally, spine-related interventions, such as lumbar fusion, have been associated with a plethora of perioperative and postoperative complications, especially with an increased comorbidity index, which could further hinder economic ability and recovery in patient populations with higher ADIs 21–23 .…”
mentioning
confidence: 99%
“…16,17 Furthermore, ADI and SES are correlated to increased comorbidity indices in populations disparaged by socioeconomic inequities. [18][19][20] Finally, spine-related interventions, such as lumbar fusion, have been associated with a plethora of perioperative and postoperative complications, especially with an increased comorbidity index, which could further hinder economic ability and recovery in patient populations with higher ADIs. [21][22][23] Although the risks for complications and other postsurgical outcomes have been well documented, with subsequent increases in the prevalence of lumbar fusions, there is a scarcity of research evaluating the impact ADI and SES on patients with degenerative spine conditions undergoing primary 1-to 2-level lumbar fusion (1-2LF).…”
mentioning
confidence: 99%